2021
DOI: 10.1371/journal.pone.0252432
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of heavy episodic drinking among female sex workers in Ethiopia: A respondent-driven sampling study

Abstract: Background Female sex workers (FSW), due to their working conditions, have an increased likelihood of heavy episodic drinking (HED), which is associated with risky sexual behavior. Nevertheless the specific contribution of HED to risky sexual behavior among FSWs in Ethiopia is not well documented for prevention activities. Objective The purpose of this study was to explore the determinants and consequences of HED among FSWs in Ethiopia. Methods A cross-sectional study using respondent-driven sampling was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 34 publications
6
17
2
Order By: Relevance
“…Reliance on condom-only as a contraceptive method by the FSWs in this study has also been reported by FSWs from other parts of the country (16). However, the condom failures were the predominant events in FSWs' lives in this study and other studies as well (15,24,43). The consequent unintended pregnancies were frequent among the FSWs in this study, as reported by other researchers (6,20,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 85%
“…Reliance on condom-only as a contraceptive method by the FSWs in this study has also been reported by FSWs from other parts of the country (16). However, the condom failures were the predominant events in FSWs' lives in this study and other studies as well (15,24,43). The consequent unintended pregnancies were frequent among the FSWs in this study, as reported by other researchers (6,20,(44)(45)(46).…”
Section: Discussionsupporting
confidence: 85%
“…All of the items were added together to get a total score that ranges between 0 and 27. The composite scores were then categorized in to levels of depression as: no depression (0-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), moderately severe depression (15)(16)(17)(18)(19) and severe depression (20-27)…”
Section: Anxiety Measurementioning
confidence: 99%
“…Condom failure is when breaking, leaking, or slipping-off occurs during penetrative sexual activity, and such failure is a frequent experience among FSWs [ 6 – 8 ]. In a study among 4,886 FSW in Ethiopia, 25.5% reported condom breakage/slippage at least once in the past month preceding the survey [ 9 ]. In the aforementioned study, heavy episodic drinking among FSWs was found to be one of the factors that increased condom breakage/slippage [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study among 4,886 FSW in Ethiopia, 25.5% reported condom breakage/slippage at least once in the past month preceding the survey [ 9 ]. In the aforementioned study, heavy episodic drinking among FSWs was found to be one of the factors that increased condom breakage/slippage [ 9 ]. Further, a study among 291 FSWs conducted in India also found that lack of experience and incorrect handling of the male condom contributed to condom breakage [ 10 ].…”
Section: Introductionmentioning
confidence: 99%